Biomechanical dysregulation of SGK-1 dependent aortic pathologic markers in hypertension - Gedney, J. Ryan; Mattia, Victoria; Figueroa, Mario; Barksdale, Christian; Fannin, Ethan; Silverman, Jonah; Xiong, Ying; Mukherjee, Rupak; Jones, Jeffrey A.; Ruddy, Jean Marie (Frontiers in Cardiovascular Medicine, 2024)
Introduction In hypertension (HTN), biomechanical stress may drive matrix remodeling through dysfunctional VSMC activity. Prior evidence has indicated VSMC tension-induced signaling through the serum and glucocorticoid inducible kinase-1 (SGK-1) can impact cytokine abundance. Here, we hypothesize that SGK-1 impacts production of additional aortic pathologic markers (APMs) representing VSMC dysfunction in HTN. Methods Aortic VSMC expression of APMs was quantified by QPCR in cyclic biaxial stretch (Stretch) +/− AngiotensinII (AngII). APMs were selected to represent VSMC dedifferentiated transcriptional activity, specifically Interleukin-6 (IL-6), Cathepsin S (CtsS), Cystatin C (CysC), Osteoprotegerin (OPG), and Tenascin C (TNC). To further assess the effect of tension alone, abdominal aortic rings from C57Bl/6 WT mice were held in a myograph at experimentally derived optimal tension (OT) or OT + 30% +/−AngII. Dependence on SGK-1 was assessed by treating with EMD638683 (SGK-1 inhibitor) and APMs were measured by QPCR. Then, WT and smooth muscle cell specific SGK-1 heterozygous knockout (SMC-SGK-1KO+/−) mice had AngII-induced HTN. Systolic blood pressure and mechanical stress parameters were assessed on Day 0 and Day 21. Plasma was analyzed by ELISA to quantify APMs. Statistical analysis was performed by ANOVA. Results In cultured aortic VSMCs, expression of all APMs was increased in response to biomechanical stimuli (Stretch +/−AngII,). Integrating the matrix contribution to signal transduction in the aortic rings led to IL-6 and CysC demonstrating SGK-1 dependence in response to elevated tension and interactive effect with concurrent AngII stimulation. CtsS and TNC, on the other hand, primarily responded to AngII, and OPG expression was unaffected in aortic ring experimentation. Both mouse strains had >30% increase in blood pressure with AngII infusion, reduced aortic distensibility and increased PPV, indicating increased aortic stiffness. In WT + AngII mice, IL-6, CtsS, CysC, and TNC plasma levels were significantly elevated, but these APMs were unaffected by HTN in the SMC-SGK-1KO+/− +AngII mice, suggesting SGK-1 plays a major role in VSMC biomechanical signaling to promote dysfunctional production of selected APMs. Conclusion In HTN, changes in the plasma levels of markers associated with aortic matrix homeostasis can reflect remodeling driven by mechanobiologic signaling in dysfunctional VSMCs, potentially through the activity of SGK-1. Further defining these pathways may identify therapeutic targets to reduce cardiovascular morbidity and mortality.